Teaching Effectively with Multimedia and its Impact on Students’ Academic Performance in Chemistry: A Case Study - Dupchu, Karma (Bhutan Journal of Research and Development, 2024)
This study investigated the impact of integrating multimedia into chemistry education in Bhutanese higher secondary schools and its influence on students’ academic performance. The research focused on assessing students’ academic performance through test scores and semi-structured interviews. A sample of 62 eleventh-grade students participated in the experimental research, which aimed to explore how multimedia applications affect the content, quality, and retention of students’ knowledge in chemistry. Data were collected by using self-administered questionnaire and achievement test. Descriptive statistics and independent samples t-test were used to analyze data. Paired samples t-test was used to analyze data. The analysis result of the pre-test showed no statistically significant differences, which in turn proves the equivalence of the two groups. The t-test result showed a significant difference between the achievements of the two groups at a significant t-value of 0.05 in the post-test. The experimental group gained higher mean scores than that of the control group. From the self-administered questionnaire, the result showed that when multimedia was integrated to teach chemistry, student displayed the high level of learning satisfaction. The findings revealed that integration of multimedia increased the academic performance and learning satisfaction of students in chemistry lessons compared to the traditional method of teaching.